Crystal structures of five 6-mercaptopurine derivatives - Gomes, Ligia R. (2016)
The crystal structures of five 6-mercaptopurine derivatives, viz. 2-[(9-acetyl-9H-purin-6-yl)sulfan-yl]-1-(3-meth-oxy-phen-yl)ethan-1-one (1), C16H14N4O3S, 2-[(9-acetyl-9H-purin-6-yl)sulfan-yl]-1-(4-meth-oxy-phen-yl)ethan-1-one (2), C16H14N4O3S, 2-[(9-acetyl-9H-purin-6-yl)sulfan-yl]-1-(4-chloro-phen-yl)ethan-1-one (3), C15H11ClN4O2S, 2-[(9-acetyl-9H-purin-6-yl)sulfan-yl]-1-(4-bromo-phen-yl)ethan-1-one (4), C15H11BrN4O2S, and 1-(3-meth-oxy-phen-yl)-2-[(9H-purin-6-yl)sulfan-yl]ethan-1-one (5), C14H12N4O2S. Compounds (2), (3) and (4) are isomorphous and accordingly their mol-ecular and supra-molecular structures are similar. An analysis of the dihedral angles between the purine and exocyclic phenyl rings show that the mol-ecules of (1) and (5) are essentially planar but that in the case of the three isomorphous compounds (2), (3) and (4), these rings are twisted by a dihedral angle of approximately 38°. With the exception of (1) all mol-ecules are linked by weak C-H⋯O hydrogen bonds in their crystals. There is π-π stacking in all compounds. A Cambridge Structural Database search revealed the existence of 11 deposited compounds containing the 1-phenyl-2-sulfanyl-ethanone scaffold; of these, only eight have a cyclic ring as substituent, the majority of these being heterocycles.